Changes of Gut Microbiota in Maintenance Hemodialysis Patients and Their Impact on Patient's Microinflammation Status: Changes of gut microbiota in maintenance hemodialysis - Zhang, Xiaopan; Wang, Yilin; Yin, Ying; Sun, Bo; Chen, Guangren; Chen, Fengling (Cellular and Molecular Biology, 2023)
This study was to investigate the changes in gut microbiota in maintenance hemodialysis patients and analyze their impact on patient's microinflammation status. For this purpose, thirty-nine chronic kidney disease (CKD) maintenance hemodialysis patients admitted to our hospital from March 2019 to March 2022 were selected as the experimental group, and 40 healthy individuals with examination results during the same period were selected as the control group. The levels of gut microbiota (Lactobacillus, Bifidobacterium, Escherichia coli, and Enterococcus faecalis) and microinflammation indicators [interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), and high-sensitivity C-reactive protein (hs-CRP)] were measured in both groups. The relationship between changes in gut microbiota and microinflammation in maintenance hemodialysis CKD patients was analyzed. Results showed that the levels of Lactobacillus and Bifidobacterium in the experimental group were significantly lower than those in the control group (all, P<0.05), while the levels of Escherichia coli and Enterococcus faecalis in the experimental group were significantly higher than those in the control group (all, P<0.05). The IL-6, TNF-α, and hs-CRP levels in the experimental group were significantly higher than those in the control group (all, P<0.05). Using microinflammation indicators as dependent variables and microbiota indicators as independent variables for stepwise regression analysis, the results showed that the levels of Lactobacillus were negatively correlated with IL-6 and TNF-α levels in patients (r=-0.358, -0.942, P<0.05); the levels of Bifidobacterium were negatively correlated with IL-6, TNF-α, and hs-CRP levels in patients (r=-0.394, -0.211, -0.547, P<0.05); the levels of Escherichia coli were positively correlated with IL-6 and TNF-α levels in patients (r=0.221, 0.268, P<0.05); the levels of Enterococcus faecalis were positively correlated with IL-6 and hs-CRP levels in patients (r=0.253, 0.378, P<0.05). In conclusion, patients with maintenance hemodialysis for CKD commonly exhibit gut microbiota dysbiosis and varying degrees of low-grade inflammation. Compared to healthy individuals, maintenance hemodialysis patients with CKD have lower levels of Bifidobacterium and Lactobacillus and higher levels of Escherichia coli and Enterococcus in their gut. Bifidobacterium, Lactobacillus, Escherichia coli, and Enterococcus all have a certain impact on the low-grade inflammation status of patients with maintenance hemodialysis for CKD.